Ethical aspects of brain death and end-of-life - Oselka,Gabriel (2007)
Abstract Ethical issues surrounding brain death and end-of-life have not been afforded in Brazil the same attention as in many developed countries. There appears to be reluctance on the part of Brazilian doctors to limit or suspend procedures or treatment which prolongs life of patients in terminal phases of severe incurable illness, or to suspend the artificial means of supporting vegetative functions in cases of brain death outside the context of organ and tissue donation for transplant. Fears grounded in possible administrative (Regional Medical Councils) or legal repercussions, as well as ambiguous interpretations of religious precepts, partially explain this reluctance which often results in unnecessary prolonging of patient suffering. A recent resolution by the Federal Medical Council on end-of-life may offer doctors some guidance and confidence in dealing with highly complex ethical situations.